Malawi : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper examines economic developments in Malawi during 1993-97. Following a short recovery in 1993, Malawi's financial situation deteriorated significantly in early 1994 as increasing problems of expenditure control ahead of its first multiparty elections and administrative problems in revenue collection led a large overall fiscal deficit mainly financed by the banking system. However, Malawi embarked, in early 1995, on an adjustment program designed to reestablish financial stability and set the basis for sustainable economic growth. Since then, the authorities' efforts have led to a significant transformation of the Malawian economy.